2001
DOI: 10.1212/wnl.57.10.1876
|View full text |Cite
|
Sign up to set email alerts
|

Surgical therapy for tremor in multiple sclerosis

Abstract: 1) QMA is a reliable, objective and valid measure of MS tremor that could be used in a clinical trial. 2) The box and blocks test can detect the improvement in prehensile function that follows surgery, but standard disability scales are poorly responsive to this change. 3) Preoperative QMA values may predict which patients are most amenable to functional improvement after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 24 publications
1
48
0
1
Order By: Relevance
“…Matsumoto and colleagues provide a review of considerations and options for measuring tremor suppression and the practical effects of DBS surgery in multiple sclerosis. 16 They present a clinical tremor rating scale, a novel quantitative movement analysis technique, and a box-and-blocks test of prehensile function Postoperative magnetic resonance imaging revealed no evidence of intraoperative haemorrhage. One additional patient had an intraoperative seizure so implantation was not completed at that time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Matsumoto and colleagues provide a review of considerations and options for measuring tremor suppression and the practical effects of DBS surgery in multiple sclerosis. 16 They present a clinical tremor rating scale, a novel quantitative movement analysis technique, and a box-and-blocks test of prehensile function Postoperative magnetic resonance imaging revealed no evidence of intraoperative haemorrhage. One additional patient had an intraoperative seizure so implantation was not completed at that time.…”
Section: Discussionmentioning
confidence: 99%
“…Multidimensional assessment appropriate to the expected range of surgical benefit is most likely to be an accurate reflection of the effects of surgery. 16 Therefore, prospective longitudinal studies using multidimensional outcome measurements are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Clinical improvement in these patients is often short lived and, in the case of multiple sclerosis, complicated by disease progression. 42,43 Although treatment for tremor targets the ventral intermediate nucleus, several studies have suggested that the posterior subthalamic area is a better location and that patients may be incidentally benefiting from electrode contacts located outside of the thalamus. 44 Overall, DBS for essential and parkinsonian tremor has been successful, while treatment of other causes of tremor has been more limited.…”
Section: Tremormentioning
confidence: 99%
“…The authors reported, "Tremors, both proximal and distal, were remarkably improved in all eight patients…" when using monopolar stimulation. Scoring used a modified clinical tremor rating scale [71]. A mean 81% tremor improvement was observed when using the best contact on each electrode.…”
Section: Posterior Subthalamic Area Stimulation With Emphasis On the mentioning
confidence: 99%